A TOUR OF ENGLISH LANGUAGE TEACHING METHODOLOGY AND ENGLISH LANGUAGE TEACHING METHODS IN SOME FOREIGN COUNTRIES (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
The paper represents an excursus in methods in teaching English, presented methods of teaching English in some foreign countries. Their advantages and disadvantages, the most effective methods of their adaptation to the specifics of the uzbek model of education are given.